SYNERGY OR CONFLICT OF LAWS? (COMPARISON BETWEEN THE COMPILATION OF RULES ON SHARI’AH ECONOMY (KHES) AND THE NATIONAL SHARI’AH BOARD’S (DSN) FATWAS) - Mudzhar, Mohamad Atho (al-'adalah, 2015)
Abstrak: Sinergi atau Konflik Hukum? (Perbandingan Kompilasi Hukum Ekonomi Syariah (KHES) dengan Fatwa Dewan Syariah Nasional (DSN). Artikel ini membandingkan Kompilasi Hukum Ekonomi Syariah (KHES) yang dibuat oleh Mahkamah Agung Indonesia pada tahun 2008 dengan fatwa yang dikeluarkan oleh Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI). Perbandingan dilakukan dalam beberapa ketentuan terutama yang menyangkut Murâbahah, Mudârabah, Ijârah, Ta’mîn, Kafâlah, Hawâlah, dan Rahn. Hal ini dilakukan karena beberapa pihak merasa khawatir jika kompilasi itu bertentangan dengan fatwa Majelis Ulama Indonesia. Hasil penelitian menunjukkan bahwa tidak terdapat konflik antara kedua regulasi di atas. Bahkan sebaliknya, mereka saling melengkapi. Perbedaan antara kedua regulasi hanya terjadi dalam tataran konseptual mengenai bentuk Murâbahah, pembatasan Murâbahah, Mushtarakah, dan definisi asuransi Syariah. Abstract: Synergy or Conflict of Laws ? (Comparison Between the Compilation of Rules on Shari’ah Economy (KHES) and the National Shari’ah Board’s (DSN) Fatwas). This article compares the Compilation of Rules on Islamic Economics (KHES) produced by the Indonesian Supreme Court in 2008 to the fatwas issued by the National Sharia Council (DSN) of the Council of Indonesian Ulama (MUI). The comparison is made in some provisions relating to Murâbaha (a particular kind of sale), Mudhârabah (partnership in a commercial enterprise), Ijârah (rent/lease/hire contract), Ta’mîn (insurance), Kafâlah (conjoining in debt guarantee), Hawâlah (transfer of debt), and Rahn (pawning/mortgage). This is done to verify whether or not the Compilation was contrary to the fatwas of Indonesian Ulama Council. The findings shows that there is no contradiction between the two regulations. The difference occurs only in the kinds of Murâbahah, Murâbahah, and Mushtarakah, as well as the definition of Ta’mîn.